2014
DOI: 10.1002/mrm.25269
|View full text |Cite
|
Sign up to set email alerts
|

T1ρ mapping for the evaluation of high intensity focused ultrasound tumor treatment

Abstract: Significant changes in tumor T1ρ were observed after HIFU treatment. These T1ρ changes were distinctly more pronounced than HIFU-induced changes in T2 . The results indicate that T1ρ imaging is sensitive to HIFU-induced tissue changes and may thus be a suitable MR method for the evaluation of HIFU treatment. Magn Reson Med 73:1593-1601, 2015. © 2014 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This can ultimately lead to extrusion of water from the treated tissue, which has been addressed previously in a study on changes in MR properties of various tissues after thermal treatment (36). In our recent study on T 1r after HIFU treatment of murine tumors, we observed signs for this denaturation-induced extrusion of water (49). While the protein denaturation itself did not lead to direct change in the tumor T 1r values, at 3 days after treatment a significant approximately 15% decrease in T 1r was observed in the treated tumors compared with baseline measurements.…”
Section: Inflammatory Response and Edema Formationmentioning
confidence: 57%
See 1 more Smart Citation
“…This can ultimately lead to extrusion of water from the treated tissue, which has been addressed previously in a study on changes in MR properties of various tissues after thermal treatment (36). In our recent study on T 1r after HIFU treatment of murine tumors, we observed signs for this denaturation-induced extrusion of water (49). While the protein denaturation itself did not lead to direct change in the tumor T 1r values, at 3 days after treatment a significant approximately 15% decrease in T 1r was observed in the treated tumors compared with baseline measurements.…”
Section: Inflammatory Response and Edema Formationmentioning
confidence: 57%
“…T 1ρ is sensitive to interactions between water molecules and macromolecules, predominantly proteins , that occur around the carrier frequency of the applied spin‐lock pulse. However, in a recent study, we did not observe a difference in tumor T 1ρ before and directly after HIFU treatment of subcutaneous mouse tumors, which suggested that T 1ρ is apparently not directly sensitive to protein denaturation occurring instantly during HIFU application .…”
Section: Mri‐detectable Hifu Treatment Effectsmentioning
confidence: 99%
“…Additional recent applications of these techniques can be found in refs. . The main strength of T 1 ρ and T 2 ρ MRI, i.e.…”
Section: Summary Of T1ρ and T2ρ Mri Techniquesmentioning
confidence: 97%
“…Additional recent applications of these techniques can be found in refs. (74,(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114)(115)(116). The main strength of T 1ρ and T 2ρ MRI, i.e.…”
Section: Summary Of T 1ρ and T 2ρ Mri Techniquesmentioning
confidence: 99%
“…In addition, we aimed to compare the performance of this optimal multiparametric analysis with conventional HIFU monitoring and evaluation methods, namely MR thermometry and contrast-enhanced MRI. Such quantitative comparison with conventional techniques could not be performed in our previous studies (13,21,22), mainly because the HIFU treatment was performed outside the MR system. In the present study, the HIFU treatment was performed in a rat tumor model on a clinical 3 T MR-HIFU system, allowing for real-time acquisition of MR temperature maps during treatment.…”
Section: Introductionmentioning
confidence: 98%